Studi Penjadwalan Produksi Untuk Efisiensi Proses Produksi pada PT. X - Gunadi, Ken (Jurnal sosial dan sains, 2025)
Production scheduling is a critical factor in manufacturing operations as it minimizes idle time and waste, thereby reducing operational costs such as overtime and excess inventory. This study aims to analyze PT. X's current production scheduling system, evaluate production efficiency, and assess sequencing methods for improving process efficiency. This study employs a descriptive-exploratory approach using sequencing analysis with four rules: FCFS (First Come First Served), SPT (Shortest Processing Time), LPT (Longest Processing Time), and EDD (Earliest Due Date). The findings reveal that PT. X currently uses FCFS scheduling, which proves suboptimal as it disregards processing time and deadlines. Despite aligning with customer demand through intermittent production process, the current efficiency rate (<1, specifically 0.82) indicates room for improvement. Analysis shows that adopting SPT scheduling would significantly improve efficiency by reducing order delays, decreasing work-in-progress backlog, and lowering penalty costs from Rp322,000 to Rp272,000. Implementing SPT scheduling would enhance production flow and cost efficiency.